Housing as a Political Tool: Gender Inequality in Student Accommodation in Iran - Parian Hoseini; Pooriya Mohseni (Critical Housing Analysis)
This paper studies the gender inequalities in university-provided student accommodation in Babolsar, Iran, in relation to the role of the dominant political power and its approach in shaping the physical form of public dormitories and the living conditions of students. Secondary data analysis based on a questionnaire survey is utilised, and the results show that in numerous physical and non-physical ways women’s public dormitories are designed and controlled in favour of the dominant political power and against the wishes of their residents. This research examines how the ideological and cultural background permeates institutional practices in housing and affects the living conditions of a disadvantaged social group, which can open a discussion on the role of housing in social exclusion.